Altered gene expression and metabolism in fetal umbilical cord mesenchymal stem cells correspond with differences in 5-month-old infant adiposity gain. Issue 1 (December 2017) - Baker, Peter; Patinkin, Zachary; Shapiro, Allison; Houssaye, Becky; Janssen, Rachel; Vanderlinden, Lauren; Dabelea, Dana; Friedman, Jacob
Abstract The intrauterine period is a critical time wherein developmental exposure can influence risk for chronic disease including childhood obesity. Using umbilical cord-derived mesenchymal stem cells (uMSC) from offspring born to normal-weight and obese mothers, we tested the hypothesis that changes in infant body composition over the first 5 months of life correspond with differences in cellular metabolism and transcriptomic profiles at birth. Higher long-chain acylcarnitine concentrations, lipid transport gene expression, and indicators of oxidative stress in uMSC-adipocytes were related to higher adiposity at 5 months of age. In uMSC-myocytes, lower amino acid concentrations and global differential gene expression for myocyte growth, amino acid biosynthesis, and oxidative stress were related to lower infant percent fat-free mass at 5 months of age, particularly in offspring of obese mothers. This is the first evidence of human infant adipocyte- or myocyte-related alterations in cellular metabolic pathways that correspond with increased adiposity and lower fat-free mass in early infancy. These pathways might reflect the effects of an adverse maternal metabolic environment on the fetal metabolome and genome. Our findings suggest that programmed differences in infant stem cell metabolism correspond with differences in body composition in early life, a known contributor to obesity risk.